Development of tobacco (Nicotiana tabacum L.) doubled haploid lines resistant to potato virus Y 0 - Shahadati-Moghaddam, Zeinalabedin; Hosseini, Azimeh; Soorni, Jahad; Trojak-Goluch, Anna (The Indian Journal of Genetics and Plant Breeding, 2016)
Viral diseases such as PotatoVirusY (PVY) in tobacco plants can cause a lot of damage annually. In order to obtain PVY resistant doubled haploids (DH) of Nicotiana tabacum with desirable traits. Two varieties of tobacco VAM resistant to PVY and K326 of recognized high quality of leaves were crossed. The F1 hybrids were grown in pots and the anthers were cultured on PGR-free MS medium. After productionÂ of somatic embryos, colchicine treatment (0.4%) was applied for 8 hours. Thereafter, 184 plantlets were transferred to greenhouse and then moved to the field and self-pollinated. The derivatives of colchicine treated and fertile plants were inoculated with PVY0. DAS-ELISA technique and rating of symptoms were used to select resistant plants. From a total of seventeen DH, seven plants were selected as pureÂ lines and evaluated under field condition. The DH lines showed significant differences between them for morphological and chemical traits. Some of the DHs had longer and wider leaves than K326 cultivar as control. The content of sugars was not affected by genotype. Finally, three doubled haploid lines (TDH-03, TDH-09, TDH-11) with desirable characteristics were selected as PVY resistance.